Ensino Baseado em Simulação interprofissional para medicação segura: ensaio clínico randomizado - Lozano, André Wilian (Universidade Federal de São Carlos, 2026)
Introduction: Interprofessional education integrated with simulation in healthcare constitutes a pedagogical strategy that favors the development of collaborative skills essential to teamwork and patient safety, especially in the context of the medication process. The available literature shows a predominance of studies with observational designs and a scarcity of experimental designs focused on interprofessional simulation for safe medication, demonstrating scientific gaps related to the experimental evaluation of these pedagogical methods, as well as their educational effects. Objective: To develop, implement, and evaluate interprofessional simulation scenarios focusing on the safe medication process for health professions students. Method: A qualitative-quantitative, analytical, experimental, prospective study, of the randomized clinical trial type, with two blinded groups (interprofessional intervention (A) and uniprofessional control (B)). The intervention consisted of applying three healthcare simulation scenarios of increasing complexity, previously constructed and validated by experts using the Delphi technique. Validated instruments for assessing interprofessional readiness (RIPLS-40), OSCE and ITOSCE for professional performance, and a validated scale of satisfaction and self-confidence were used, with appropriate inferential statistical analysis for intragroup and intergroup comparisons. The research was conducted with the approval of the Research Ethics Committee. Results: 57 students from Nursing, Medicine, and Pharmacy participated. Three healthcare simulations were conducted focusing on critical steps in the safe medication process, led by previously trained facilitators. A statistically significant increase in readiness for interprofessional learning and observable performance improvements related to medication reconciliation, prescription, preparation, administration, medication monitoring, and identification of avoidable errors were observed in both groups. The performance gains identified in the immediate post-test (30 days) were maintained in the late post-test (90 days), indicating retention of learning. No statistically significant differences were identified between the interprofessional and uniprofessional groups, indicating educational equivalence between active pedagogical formats. Additionally, high levels of student satisfaction and self-confidence were observed. Conclusion: Intentionally planned, expert-validated, and interprofessional education-based healthcare simulation proved effective in developing collaborative competencies related to medication safety, promoting significant gains in observable professional performance and readiness for interprofessional learning. Both interprofessional and uniprofessional simulations promoted consistent intragroup advancements, demonstrating educational equivalence between active approaches. The absence of a statistically significant difference between the groups indicates non-rejection of the null hypothesis. This investigation advances the state of the art by integrating, in an unprecedented way in the Brazilian context, the construction, validation, and experimental evaluation of interprofessional simulation scenarios focused on medication safety, representing, to the best of our knowledge, the first randomized clinical trial conducted in the country with this focus. The findings have the potential to impact health education and the improvement of interprofessional practices, with implications for promoting patient safety, improving health education, and strengthening health systems.
Interprofessional Simulation-Based Education for medication safety: a randomized controlled trial
Keywords: Educação interprofissional; Ensino superior; Segurança do paciente; Erros de medicação; Treinamento por simulação; Interprofessional education; Higher education; Patient safety; Medication errors; Simulation training; CIENCIAS DA SAUDE::ENFERMAGEM; 3. Saúde e Bem-Estar